CORPORATION AS THE ACTORS OF FISHERIES CRIME IN INDONESIA - Retno Ningsih, Sri Dwi; Supanto, S.; Latifah, Emmy (Jurnal Dinamika Hukum, 2018)
In Indonesia, the Corporation is already recognized as one of the perpetrators of criminal acts in a variety of specific criminal acts and regulations, including in the Fisheries Act. Article 1 paragraph (14) Act No. 31 of the year 2004 jo Act No. 45 of the year 2009 about fisheries States that every person is a person, the individual or Corporation. This research is normative juridical research. The approach used is statute approach.The results showed that in the theory of criminal law, there is some form of the position of the Corporation as the perpetrator of a criminal offence may be subject to iability. The purpose of this study is to examine how the legal position of the Corporation as the perpetrator of the criminal offence of fishing in Indonesia. This research is the normative legal research. The data used are secondary data, while data collection is done through the study of the literature. Data analysis techniques using the deductive approach of law and interpretation.Keywords: corporations, criminal act fisheries